1994
DOI: 10.1007/bf01704698
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Gram negative noscomial bronchopneumonia by intratracheal colistin in critically ill patients

Abstract: This study suggests that the administration of intratracheal colistin during a 2-week period significantly reduces the incidence of Gram-negative BPN without creating an increasing number of BPN due to colistin-resistant micro-organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 23 publications
1
39
1
1
Order By: Relevance
“…Intratracheal colistin, as opposed to inhaled colistin, has also been shown to reduce the incidence of nosocomial pneumonia by 10 to 25% in critically ill patients undergoing mechanical ventilation. Emergence of colistin-resistant organisms was not observed in this study (323).…”
Section: Nosocomial Pneumoniacontrasting
confidence: 64%
“…Intratracheal colistin, as opposed to inhaled colistin, has also been shown to reduce the incidence of nosocomial pneumonia by 10 to 25% in critically ill patients undergoing mechanical ventilation. Emergence of colistin-resistant organisms was not observed in this study (323).…”
Section: Nosocomial Pneumoniacontrasting
confidence: 64%
“…Few studies have investigated pneumonia prophylaxis with antibiotics administered to the airways in critical care [9][10][11]. ROUBY et al [9] instilled colistin within the tracheal tube and decreased the incidence of bronchopneumonia due to GNB; however, they used digestive selective decontamination in addition to tracheal instillation.…”
Section: Discussionmentioning
confidence: 99%
“…ROUBY et al [9] instilled colistin within the tracheal tube and decreased the incidence of bronchopneumonia due to GNB; however, they used digestive selective decontamination in addition to tracheal instillation. KLICK et al [10] sprayed polymyxin B in the trachea/pharynx and found decreased GNB-pneumonia in a mixed population of intubated and non-intubated patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations